2006
DOI: 10.1186/cc5111
|View full text |Cite
|
Sign up to set email alerts
|

Early changes of CD4-positive lymphocytes and NK cells in patients with severe Gram-negative sepsis

Abstract: Introduction Our aim was to define early changes of lymphocytes and of NK cells in severe sepsis and to correlate them with serum levels of soluble triggering receptor expressed on myeloid cells-1 (sTREM-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 20 publications
4
36
3
Order By: Relevance
“…We observed that NK lymphopenia was reported in most previous studies and it is hypothesized that NK cells migrate from the blood to inflamed tissue [31]. This NK lymphopenia was part of a global lymphopenia that involved B and T lymphocytes, which was more severe among septic patients and among non-survivors within the overall ICU population, as has been already reported [19], [31]. Conversely, and in agreement with the results of de Pablo et al [39], we could not observe any correlation between the numbers of circulating NK cells on admission and ICU mortality (even in the septic patients), as recently reported in a recent study [18].…”
Section: Discussionsupporting
confidence: 80%
“…We observed that NK lymphopenia was reported in most previous studies and it is hypothesized that NK cells migrate from the blood to inflamed tissue [31]. This NK lymphopenia was part of a global lymphopenia that involved B and T lymphocytes, which was more severe among septic patients and among non-survivors within the overall ICU population, as has been already reported [19], [31]. Conversely, and in agreement with the results of de Pablo et al [39], we could not observe any correlation between the numbers of circulating NK cells on admission and ICU mortality (even in the septic patients), as recently reported in a recent study [18].…”
Section: Discussionsupporting
confidence: 80%
“…This decrease is the reflection of a general lymphopenia and may be due to the trafficking of NK cells to the sites of infection [46], or to apoptosis [47]. Interestingly, some reports suggest that NK cell percentages or counts are associated with outcome [48]. Our work further establishes that the decrease is similarly observed for both CD56 bright and CD56 dim NK cells subsets.…”
Section: Discussionsupporting
confidence: 72%
“…These facts explain why this cell subset has not been heavily investigated in sepsis 94,95 . Studies indicate that both CD56 hi and CD56 low NK cell subsets are affected during sepsis; the number of circulating NK cells is markedly decreased in septic patients 96,97 , which frequently persists for weeks 98 and is associated with increased mortality 99 . Furthermore, the absolute number of both NK cell subsets is decreased in sepsis 100 .…”
Section: Impact Of Sepsis On Immune Cellsmentioning
confidence: 99%